2020
DOI: 10.3892/or.2020.7497
|View full text |Cite
|
Sign up to set email alerts
|

A radiomics model to predict the invasiveness of thymic epithelial tumors based on contrast‑enhanced computed tomography

Abstract: In the present study, we aimed to construct a radiomics model using contrast-enhanced computed tomography (CT) to predict the pathological invasiveness of thymic epithelial tumors (TETs). We retrospectively reviewed the records of 179 consecutive patients (89 females) with histologically confirmed TETs from two hospitals. The 82 low-and 97 high-risk TETs were assigned to training (90 tumors), internal validation (49 tumors) and external validation (40 tumors) cohorts. Radiomics features extracted from preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…and J.L., with 9 and 10 years of experience in thoracic imaging, respectively). The interobserver agreement was assessed by using Cohen kappa test, where 0-0.2 was slight agreement, 0.21-0.40 fair agreement, 0.41-0.60 moderate agreement, 0.61-0.80 substantial agreement, and 0.81-1.00 almost perfect agreement [19]. The discriminatory power for the three methods was compared.…”
Section: Internal Validation and Clinical Utility Of Clinical And Commentioning
confidence: 99%
“…and J.L., with 9 and 10 years of experience in thoracic imaging, respectively). The interobserver agreement was assessed by using Cohen kappa test, where 0-0.2 was slight agreement, 0.21-0.40 fair agreement, 0.41-0.60 moderate agreement, 0.61-0.80 substantial agreement, and 0.81-1.00 almost perfect agreement [19]. The discriminatory power for the three methods was compared.…”
Section: Internal Validation and Clinical Utility Of Clinical And Commentioning
confidence: 99%
“…Similar to this textural studies, radiomics models have already been used to stage tumors and predict lymph node metastasis and prognosis [ 20 23 ]. A few studies have used radiomics models to predict the pathological invasiveness of TETs [ 24 ]. Although some previous studies have demonstrated that a textural analysis based on CT images can be used to differentiate high-risk TETs from low-risk TETs, they only analyzed 2D textural features, and their sample sizes were small [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics models have already been used to stage tumors and predict lymph node metastasis and prognosis [19][20][21][22]. A few studies have used radiomics models to predict the pathological invasiveness of TETs [23]. Although some previous studies have demonstrated that a textural analysis based on CT images can be used to differentiate high-risk TETs from low-risk TETs, they only analyzed 2D textural features, and their sample sizes were small [24,25].…”
Section: Discussionmentioning
confidence: 99%